2008
DOI: 10.1258/la.2007.06008e
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Corynebacterium kutscheri in the faeces of subclinically infected mice

Abstract: SummaryMice were infected experimentally and subclinically with Corynebacterium kutscheri to recover the organism from mice faeces. The faeces were then cultured using selective furazolidone-nalidixic acid-colimycin agar. The number of C. kutscheri per gram of fresh faeces varied from mouse to mouse, but once established in the intestine, the organism was excreted in the faeces for at least five months. Viable bacteria were detected in most of the faecal samples, including those stored in the animal room for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This type includes species pathogenic for animals, e.g. C. pseudotuberculosis (Baird & Fontanie, 2007;Nieto et al, 2009), C. kutscheri (Amao et al, 2008;Suzuki et al, 1988), C. canis (Funke et al, 2009) and a very large group of species colonizing the skin and mucous membranes of man, which in favorable circumstances, may become the cause of serious infections in humans. These opportunistic organisms, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This type includes species pathogenic for animals, e.g. C. pseudotuberculosis (Baird & Fontanie, 2007;Nieto et al, 2009), C. kutscheri (Amao et al, 2008;Suzuki et al, 1988), C. canis (Funke et al, 2009) and a very large group of species colonizing the skin and mucous membranes of man, which in favorable circumstances, may become the cause of serious infections in humans. These opportunistic organisms, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The same problem plagued C. kutscheri , another well-known pathogenic Corynebacterium which can cause pseudotuberculosis [ 5 ]. C. kutscheri is usually a regular testing item in microbiological health monitoring and is very well controlled in Korean laboratory animal facilities [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…in experimental mice and rats is not well described, some studies on pathogenic Corynebacterium have been reported. For example, C. kutscheri can cause pseudotuberculosis, characterized by rough hair coat, slowed activity, leanness, and hyperpnea [ 5 ]. In addition, Corynebacterium -associated hyperkeratosis (CAH), caused by C. bovis , has been the subject of reports in recent decades [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis In infected colonies, C. kutscheri will typically cause latent infections and may be detected by PCR or cultured from submaxillary (cervical) lymph nodes, oropharynx and nasopharynx, middle ears, and preputial glands of feces (Amao et al, 1995(Amao et al, , 2002(Amao et al, , 2008. Latent infections may be triggered to become clinical by a variety of stressors that can cause immunosuppression in the host.…”
Section: Pseudotuberculosismentioning
confidence: 99%